Toward the use of the contraposition law in multi-adjoint lattices - Madrid-Labrador, Nicolás Miguel (My University, 2017)
A study of the contraposition rule in fuzzy logic by means of adjoint triples.
Keywords: Lógica difusa; Contraposition rule; Fuzzy logic